VeritasPrepKarishma wrote:

zatspeed wrote:

If Y = 2 + 2K and Y(not equal to) 0 , Then 1/Y + 1/Y + 1/Y + 1/Y = ?

You should give the options.

1/Y + 1/Y + 1/Y + 1/Y

= 4/Y

= 4/(2 + 2K)

= 2/(1 + K)

Responding to a pm:

**Quote:**

For you last two steps, this involves using the conjugate of the denominator and then recognizing that 1-k2 can be expressed as a difference of squares, correct?

The question gives you that

\(Y = 2 + 2K\)

So you simply substitute that in place of Y in the denominator.

\(\frac{4}{Y} = \frac{4}{(2 + 2K)}\)

Then just take 2 common from the numerator and denominator to get:

\(\frac{4}{(2 + 2K)} = \frac{2*2}{2(1 + K)}\)

Cancel off the 2 of the numerator with the 2 of the denominator to get:

\(\frac{2*2}{2(1 + K)} = \frac{2}{(1 + K)}\)

_________________

Karishma

Veritas Prep GMAT Instructor

Learn more about how Veritas Prep can help you achieve a great GMAT score by checking out their GMAT Prep Options >

GMAT self-study has never been more personalized or more fun. Try ORION Free!